Global profiling of SRP interaction with nascent polypeptides - Schibich, Daniela; Gloge, Felix; Pöhner, Ina; Björkholm, Patrik; Wade, Rebecca C.; Heijne, Gunnar von; Bukau, Bernd; Kramer, Günter (Nature, 2016)
Here, the selection of substrates by the protein-RNA complex known as the signal recognition particle (SRP) is investigated in the bacterium Escherichia coli, revealing that the SRP has a strong preference for hydrophobic transmembrane domains of inner membrane proteins.